Wnt/β-catenin signaling pathway is involved in induction of apoptosis by oridonin in colon cancer COLO205 cells - Bu, Heqi; Liu, Dianlei; Cui, Junhui; Cai, Ke; Shen, Feng (Translational Cancer Research, 2019)
Background: Oridonin has been demonstrated to have anticancer effect on all kinds of cancer cells and it has shown anti-tumor activity in some tumors partially via the inactivation of Wnt/β-catenin signaling pathway. The study investigated the anticancer effect of oridonin on colon carcinoma cell line COLO205 and explored underlying mechanism. Methods: Cell Counting Kit-8 (CCK-8) assay was performed to assess cell viability. Flow cytometry was performed to analyze the apoptosis. The key target genes and proteins involved in Wnt/β-catenin pathway were detected by quantitative polymerase chain reaction (qPCR) and Western blotting. The xenograft tumor model of colon cancer COLO205 cell was introduced to detect anti-tumor effects in vivo. Transferase-mediated dUTP nick end labeling (TUNEL) assay was adopted to test the apoptotic cells in the tumor tissues. Results: Oridonin inhibited the proliferation of colon cancer COLO205 cells in a dose-dependent and time-dependent manner. Oridonin induced apoptosis by increasing the cleavage of caspases in vitro. Furthermore, the expression levels of β-catenin and its downstream targets, including c-myc, cyclinD1 and survivin were significantly reduced. Nevertheless the knockdown of β-catenin by specific small interfering RNA (siRNA) could augment the anti-proliferative and pro-apoptotic effects by oridonin in COLO205 cells. Meanwhile, oridonin also increased protein expression level of glycogen synthase kinase 3β (GSK3β) and decreased the phosphorylation level of GSK3β. In vivo, oridonin treatment significantly suppressed tumor growth of COLO205 cell xenografts, and which was accompanied by the restrain of Wnt/β-catenin pathway. Conclusions: Our present study demonstrated that the growth inhibition and apoptosis induction in colon cancer COLO205 cells by oridonin could be partially mediated through discontinuing Wnt/β-catenin signaling pathway.